La iconografía de Trifonte en el gótico final en los reinos de León y Castilla (Estudios humanísticos. Geografía, historia y arte, 1991)
The three-faces man, a very common subject in gothic works of art from the late fifteenth century, combines the interest in pure ornamentation with a simbolism that is based on the relation profane-religious iconography, in the field of the discoveries of new Lands and the representation of fantastic creatures.